The study of research fund absorption by Iranian educational and research organizations - Hajar Sotodeh; Mohammad Hasan Omidi (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2014)
Introduction: Given the crucial role of financial aids and grants in research progress, the present communication attempts to study the research funding situation in Iran during 2008-2011. Research method: The present paper applies a scientometric method to study the data related to Iranian scientific productions extracted from Science Citation Index Expanded. The data are analyzed using Excel and SPSS, based on descriptive and inferential statistics. Results: The findings reveal that more than 30 percent of Iranian scientific papers are supported by research funds, of which about 25 percent are internationally funded. The highest ranked universities in terms of the amount of funded papers, especially by foreign resources, largely consist of those based in capital, along with Azad Islamic University. They are, also, revealed to be the most successful in collaborating with foreign organizations in providing research grants and aids. Conclusions: Given the low number of funded papers, Iranian researchers are required to endeavor seriously to absorb more research funds, especially from foreign states and international organizations. Research instruments and equipments being very expensive in many disciplines, researchers’ attempts to absorb foreign resources can be an appropriate solution to overcome financial shortage and instrumental poverty in scientifically developing countries.